Composition-specific granulation characteristics of molten slag at improved throughput and high temperature of 1,723 K - Junjun Wu; Yu Tan; Yuxiang Fu; Hong Wang; Xun Zhu; Qiang Liao (Energy Storage and Saving, 2023)
Centrifugal granulation is one key step to enable waste heat recovery from the molten slag in the iron and steel industry. Yet, it remains unknown about the granulation characteristics of molten slag with different chemical compositions, especially at high throughput. In this work, we provided an experimental study on centrifugal granulation with four types of molten slags. The stage-specific centrifugal granulation was recorded and analyzed at first. Both effects of atomizer configuration and chemical compositions on granulation were investigated in detail. The cup-type atomizer favors film-mode disintegration and possesses better anti-adhesion capacity although the final granule size was not strongly affected by the atomizer configuration. Most importantly, centrifugal granulation has been demonstrated with appreciable adaptability to composition-specific blast furnace (BF) slag with binary basicity of 0.9–1.3. The present study not only sheds light on the modest effect of the chemical composition of molten slag on centrifugal granulation characteristics, but also gains credit for the adaptivity of CGATER.